Populasi dan Spesies Serangga Hama di Gudang dengan Penciri Atap, Lantai, dan Ventilasi yang Berbeda di Tiga Pasar Lokal pada Kecamatan Alang-Alang Lebar dan Sukarame, Kota Palembang Sumatera Selatan - Nabila, Ade; Herlinda, Siti; Yulistin, Eka; Setyawati, Anita; Oktaviani, Oktaviani; Anggraini, Erise; Prim Suardi Yudanto, Marcelinus Rido; Aulia Chandra, Fachdilla; Raffi, Muhammad; Az Zahra, Aisyah Dwi; Meitha Sari, Dwi (Seminar Nasional Lahan Suboptimal, 2024)
Nabila, A., Herlinda, S., Yulistin, E., Setyawati, A., Oktaviani, O., Anggraini, E., Yudanto, M. R. P. S., Chandra, F. A., Raffi, M., Az Zahra, A. D., Sari, D. M. (2024). population and storage pest species from three local markets with various roofs, floors, and ventilations in Sub-district of Alang-Alang Lebar and Sukarame, Palembang South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 679–689). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Storage insects provide a substantial risk to food spoiling, potentially resulting in a considerable reduction of up to 82.5% in food preservation. Ventilation is essential to avert harm caused by storage insect infestations. This study aimed to identify species and assess the population of storage pest insects in relation to the kind of ventilation in the Alang-Alang Lebar and Sukarame market's storage facilities. This study employed a direct collecting strategy for insects spotted on each food product commodity through handpicking, followed by the identification of each obtained sample. The identified bug species vary due to the diversity of dietary products. Species such Sitophilus oryzae and Tribolium castenum were predominant, alongside several others such as Cryptolestes ferrugineus, Carpophilus dimidiatus, Callosobruchus chinensis, Rhyzopertha dominica, and Oryzaephilus surinamensis. In the rice commodities market in Alang Alang Lebar District, the storage pest species S. oryzae was identified. S. oryzae is an insect pest that inflicts damage on stored rice. Sitophilus oryzae was found as the insect pest responsible for the majority of damage to stored rice. The peanut commodities in the Kebun Bunga Market and KM 5 Market comprised the species C. dimidiatus. C. dimidiatus was a significant pest that infests dry grains and fruits after harvest. The yield loss resulting from the assault of C. dimidiatus was quite substantial. Fermented peanut products were found as the primary target of C. dimidiatus. Seven species were identified in the storage with filtered ventilation. The pest insects infestation was deemed low due to the relatively small population, indicating the efficacy of both natural and filtered ventilation systems.